Meta-analysis. Issue 1 (31st December 2022) - Hagger, Martin
ABSTRACT: The sheer volume of available research and shifts toward evidence-based practice has led researchers and practitioners in sport and exercise psychology to rely increasingly on meta-analyses to summarize current knowledge, provide future research directions, and inform policy and practice. These issues highlight the imperative of precision and integrity in the conduct of meta-analyses in the discipline. This review provides a summary of meta-analytic methods relevant to sport and exercise psychology, identifies important issues and advances in meta-analytic methods, and provides best practice guidelines for meta-analysts to consider when synthesizing research in the discipline. In Part I, I provide an overview of the basic principles of meta-analysis and direct readers to accessible, non-technical treatments of the topic. In Part II, I introduce several key issues in meta-analysis and summarize the latest advances in each: effective assessment of heterogeneity; testing for moderators; dealing with dependency; evaluating publication bias and tracking down 'fugitive literature'; and assessing sample size in meta-analysis. I also cover two emerging topics: testing theories using meta-analysis and open science and transparency practices in meta-analysis. I conclude the discussion of each issue by providing best practice guidelines, and refer the reader to further accessible texts to augment knowledge and understanding.